Volatile metabolic profiling of SA Chenin blanc fresh and fruity and rich and ripe wine styles : development of analytical methods for flavour compounds (aroma and flavour) and application of chemometrics for resolution of complex analytical measurements - Lawrence, Nina (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2012